Two new Aprostocetus species (Hymenoptera: Eulophidae: Tetrastichinae), fortuitous parasitoids of invasive eulophid gall inducers (Tetrastichinae) on Eucalyptus and Erythrina - Yang, Man-Miao; Lin, Yu-Che; Wu, Yaojun; Fisher, Nicole; Saimanee, Titiporn; Sangtongpraow, Benjakhun; Zhu, Chaodong; Chiu, William Chien-Hsien; Salle, John La (Zootaxa, 2014)
Two closely related new species of Aprostocetus Westwood (Hymenoptera: Eulophidae: Tetrastichinae) are described as fortuitous parasitoids of invasive gall inducers in two other genera of Tetrastichinae, Leptocybe Fisher & LaSalle and Quadrastichus Girault. Aprostocetus causalis La Salle & Wu is a parasitoid of Leptocybe invasa Fisher & La Salle on Eucalyptus spp. (Myrtaceae) in China and Thailand, and A. felix La Salle, Yang & Lin is a parasitoid of Quadrastichus erythrinae Kim on Erythrina spp. (Fabaceae) in Taiwan. Epitetrastichus nigriventris Girault, 1913 is removed from synonymy from Aprostocetus gala (Walker), and treated as the valid species A. nigriventris (Girault).